The importance of administrative justice rights in international refugee law: a case study of South Africa - Harris, Thomas (Department of Public Law, 2019)
International human rights law instruments are not prescriptive regarding the procedure for processing refugees by an individual state. However, they do provide an extensive set of rights, and it is these rights that form the focus of this study. One of the main principles of international law is to protect human rights and human dignity. In the South African context, the Promotion of Administrative Justice Act 3 of 2000 (‘PAJA’) reinforces section 33 of the Constitution, the objective of which is to provide just administrative action for everyone – whether they are South African nationals or otherwise. The Department of Home Affairs (‘DHA’) is responsible for processing refugee applications under the Refugees Act 130 of 1998, and as a public body performing a public function it is obliged to adhere to the laws prescribed by PAJA. The Refugees Act states in the preamble the intention for the law to give effect to the relevant international legal instruments to which South Africa is party and the principles and standards relating to refugees contained within. These international instruments are the 1951 Convention Relating to the Status of Refugees, the 197 Protocol Relating to the Status of Refugees and the 1969 Organization of African Unity Convention Governing the Specific Aspects of Refugee Problems in Africa. The preamble of the Refugees Act also refers to ‘other human rights instruments’ which includes legislation such as the 1966 International Covenant on Civil and Political Rights and the 1966 International Covenant on Economic, Social and Cultural Rights. It is the recognition of the obligations assumed under the international instruments, combined with domestic legislation in PAJA and the Constitution, that provide a stringent set of rights designed to give refugees appropriate administrative justice by way of having applications processed and decided upon according to the law, including reviews and appeals if necessary. As is apparent from many studies and scholarly articles on this topic, refugees seeking protection in South Africa are not always treated as the law intended. This has a number of different consequences, some of which can pose a danger to life. This emphasises the gravity of making the correct legal decision on a refugee application. This study will focus on the procedural failings of the DHA, and how these failings often amount to insufficient administrative justice and in turn fail to provide refugee applicants with the rights to which they are entitled. The study examines this issue from a human rights and human dignity perspective – both of which are materially affected by the absence of administrative justice rights.